Amazon Oils from Andiroba (Carapa sp.) and Babassu (Orbignya sp.) for Preparation Biodiesel by Enzymatic Catalysis - Ferreira, Adriana M.; da S. Sena, Iracirema; Magalhães, Keurison F.; Oliveira, Samuel L.; Ferreira, Irlon M.; Porto, André L.M. (Current Biotechnology, 2018)
Background: Biodiesel represents an alternative energy source with economic, social, environmental, and technological advantages over nonrenewable fuels. Objective: This study investigated two oils derived from plants of the Brazilian Amazon, andiroba (Carapa sp.) oil and babassu (Orbignya sp.) oil, as possible triacylglyceride sources for the production of biofuels by lipase B from Candida antarctica (CALB). Methods: The production of biodiesel ethylic by enzymatic catalyst was carried out in 3-mL Erlenmeyer flasks containing 150 mg (154 μL) of either babassu or andiroba oil, 475 μL of ethanol, and 15 mg of CALB. Results: The physical, chemical, and spectroscopic properties of these oils and their resulting biofuels were also reported. CALB exhibited high activity in the alcoholysis of babassu and andiroba oils under mild conditions and produced biodiesel ethyl esters in high yields (90% and 94%, respectively). The oils and biodiesel were characterized using 1H NMR, Chromatography Gas–Mass Spectrometry (CGMS), Fourier Transform Infrared Spectroscopy (FT-IR), and thermogravimetric analysis (TGA) being the main findings of the study. Conclusion: Ethanolysis of babassu and andiroba oils by catalysis enzymatic (CALB), showed to be a successful route in the synthesis of ethylic biodiesel in high yield. The corresponding biodiesels were characterized by 1H NMR spectra, GC-MS, FT-IR, and TGA analyses. Results described here provide relevant information for the further research uses andiroba and babassu oils, the alternatives to other oils in synthesis of biodiesel.
Keywords: transesterification